(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the relationship between national character and mobility as a basis for the rise of the nation. Social mobility, in turn, elevates the character of the nation. These processes interact to form the strong will of the nation.